2020
DOI: 10.4038/cjs.v49i2.7740
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and selected chemical properties of the flowers of three different varieties of Butterfly Pea (<i>Clitoria ternatea</i> L.)

Abstract: Butterfly pea (Clitoria ternatea L.) is used for production of herbal teas, herbal juices and having a potential to use in culinary purposes. Even though, it is grown widely in Sri Lanka, comprehensive information and studies conducted on three popular varieties are still lacking. Hence, the aim of this study was to evaluate the elemental compositions, phytochemical properties of three C. ternatea L. flower varieties grown in Sri Lanka; white flower with normal keel petals (WSPF), blue flower with normal keel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(22 reference statements)
1
1
0
1
Order By: Relevance
“…The TPC content of raw YP was 3.0 ± 0.1 mg GAE/g (db) which is in line with the previously reported range (2.2–9.1 mg GAE/g) for split and whole yellow peas of different particle sizes [ 33 ]. As expected, the raw BP contained a much higher amount of TPC than YP with a value of 49.2 ± 0.8 mg GAE/g (db), again in agreement with the TPC range reported for BP in the literature [ 34 , 35 ]. It has also been reported that the TPC content of the raw BP greatly depends on variety [ 35 ], extraction solvent used, e.g., water or methanol [ 36 ], and extraction method, e.g., ultrasound or water bath [ 34 ].…”
Section: Resultssupporting
confidence: 89%
“…The TPC content of raw YP was 3.0 ± 0.1 mg GAE/g (db) which is in line with the previously reported range (2.2–9.1 mg GAE/g) for split and whole yellow peas of different particle sizes [ 33 ]. As expected, the raw BP contained a much higher amount of TPC than YP with a value of 49.2 ± 0.8 mg GAE/g (db), again in agreement with the TPC range reported for BP in the literature [ 34 , 35 ]. It has also been reported that the TPC content of the raw BP greatly depends on variety [ 35 ], extraction solvent used, e.g., water or methanol [ 36 ], and extraction method, e.g., ultrasound or water bath [ 34 ].…”
Section: Resultssupporting
confidence: 89%
“…Faktor lain yang dapat mempengaruhi aktivitas antioksidan ekstrak bunga telang (Clitoria ternatea L.) adalah perbedaan varietas tanaman telang yang digunakan yang dapat menghasilkan aktivitas antioksidan yang juga berbeda. Dalam penelitian (11), dilakukan pengujian aktivitas antioksidan terhadap 3 varietas bunga telang (Clitoria ternatea L.) yaitu pada bunga putih kelopak normal, bunga biru kelopak normal, dan bunga biru kelopak yang membesar dengan nilai IC 50 berturut-turut sebesar 27,38 ppm; 51,92 ppm; dan 23,75 ppm. Berdasarkan hasil penelusuran pustaka, dapat diketahui aktivitas paling tinggi dihasilkan oleh bunga telang (Clitoria ternatea L.) berwarna biru dengan kelopak yang membesar yang ditunjukkan oleh nilai IC 50 sebesar 23,75 ppm.…”
Section: Hasil Penelitian Dan Pembahasan Aktivitas Antioksidan Bunga ...unclassified
“…Anthocyanin-rich fractions of C. ternatea flowers were effective against P. aeruginosa with significant biofilm inhibitory activity of 64.0 ± 1.1% (Jeyaraj et al, 2022b). For their significant antioxidant activity, Lakshan et al (2020) measured the total phenolic content (TPC), total flavonoid content (TFC), ferric-reducing antioxidant power (FRAP), and DPPH radical scavenging activity of three varieties of Sri Lankan C. ternatea, including white flower with normal keel petals (WSPF), blue flower with normal keel petals (BSPF), and blue flower with enlarged keel petals (BMPF). They revealed that these three flower types had considerable concentrations of biologically active compounds, which suggests that the flower samples had significantly greater concentrations of TPC, TFC, and free radical scavenging activity.…”
Section: Introductionmentioning
confidence: 99%